The Biophysical Efficacy of Smart Phones on the Eyes of Children from 3-12 Years - Munther Sameen Shuker1, Zina Tariq Ali2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The modern day electronic gadget like laptops, smart phones (which offers advanced Technologies’ withfunctionality similar as a personal computer), TV, computer games that held by hand, … etc. that completelyinfluence the vision, a books or a newspaper that read is healthier than reading taken away the electronicdevices due to the printing materials are typically great in divergence while the electronic screen contentmentapproach with drop contrast and thus needs further optical focus as well as added strain to the eye. In thecurrent study , we assess the biophysical effectiveness of mobile phone on children up to 12 years, thecurrent study was enrolled fifty (50) children, the information were taken as (age, gender, time of usingmobile phone in hours, at which time the child use mobile phone day or night, visual acuity, family history,symptoms). Many optical devices used to obtain precise measurements from the patients which included(Snellen chart, autorefractometer, retinoscope, trial case, E card test, finger cube test, hand card test, catforddrum test, Sheridan gardiner test and prism bar).After conducting the necessary statistical methods and tests, it revealed that the most factor has more effectis the number of hours of using mobile phone devices and the children between (6-8) years were the mostused mobile phone devices.